Reliability of the Buttock Applied Strain Test to Diagnose Radicular Pain in Patients With Low Back Pain. Issue 8 (29th April 2020) - Samolsky Dekel, Boaz Gedaliahu; Sorella, Maria Cristina; Vasarri, Alessio; Melotti, Rita Maria
Abstract: Background: Low‐back pain (LBP) pathophysiological conditions include nociceptive back pain, somatic referred pain, radicular pain (RP), and radiculopathy. Differential diagnosis is challenging; guidance may come from patients' thorough clinical history and physical examination and, particularly for lumbar RP, from the evaluation of subjective responses of injured lumbar nerves to a strain applied at the buttock (buttock applied strain [BUAS] test). Methods: In a sample of 395 consecutive patients with LBP, sensitivity, specificity, and prior probability (positive predictive values [PPVs] and negative predictive values [NPVs]) of the BUAS test were evaluated against 2 reference tests: the straight leg raising test (SLRT) and the painDETECT (PD) questionnaire. Multinomial logistic regression (MLR) and χ 2 analyses were used to evaluate the BUAS test outcomes' dependence upon independent variables (gender, age group, pain localization, SLRT outcomes, and PD outcomes). Cohen's kappa statistic was used to assess inter‐rater agreement. Results: Compared with the PD questionnaire, the BUAS test showed a sensitivity of 92%, specificity of 100%, PPV of 100%, and NPV of 82%; compared with the SLRT, the BUAS test showed a sensitivity of 82%, NPV of 82%, specificity of 40%, and PPV of 40%. Inter‐rater agreement of Cohen's kappa was 0.911. Significant associations were found between BUAS test outcomes and pain localization, SLRT outcomes, and PD outcomes, but not with the predictors gender or age group. MLR showed significant congruent relationships between BUAS test and PD outcomes. Conclusion: Among patients with LBP, the BUAS test showed satisfactory sensitivity, specificity, prior probability, and inter‐rater reliability; thus, it may be considered a useful adjunctive tool to diagnose RP in patients with LBP. For more generalized results, more research, in clinical settings other than pain clinics, is needed.